Marine priority habitat mapping in a Mediterranean conservation area (Gyaros, South Aegean) through multi-platform marine remote sensing techniques - Dimas, Xenophon; Fakiris, Elias; Christodoulou, Dimitris; Georgiou, Nikos; Geraga, Maria; Papathanasiou, Vasillis; Orfanidis, Sotiris; Kotomatas, Spyros; Papatheodorou, George (Frontiers in Marine Science, 2022)
The aim of this study is to present the results of the first complete marine habitat mapping through marine remote sensing techniques in Gyaros Island; a remote island in the Cyclades archipelago with great historical and ecological value. Gyaros Island is of great biological importance and for this reason since 2011 is part of the NATURA 2000 network and by 2019 is characterised as a Marine Protected Area (MPA).More than 80 km2 of seafloor area were inspected through a multi-platform marine remote sensing techniques survey through two individual expeditions in 2014 and 2017. The remote sensing survey was conducted utilising Side Scan Sonar, Sub Bottom Profiler and Multi and Single Beam Echosounders. In addition to the remote sensing survey, an extensive ground truth network was established utilising Underwater Towed Camera and VanVeen Sediment Grabber. These resulted in the area being fully covered with high-quality data. Through these a classification of the area was performed based on three distinct seafloor habitat mapping schemes (Expert, Eunis and NATURA HD). The survey and the classification revealed that over 50% of the seafloor is covered by P.oceanica meadows and coralligenous and other calcareous bio-concretions priority habitats. Also, based on the results of this work, Gyaros MPA was established and different protections and conservation zones were set.